IMPLEMENTATION OF THE EMERGENCY RESPONSE PROGRAM TO ACHIEVE COMMUNITY INDEPENDENCE IN ROBAN VILLAGE, CENTRAL SINGKAWANG DISTRICT - Ruby Albalad. HS (PT. Jurnal Center Indonesia Publisher, 2026)
The purpose of this study is to describe and analyze the process of organizing, interpreting and applying the implementation process of the Active Emergency Village program in realizing community independence in Roban Village, Singkawang City. The results of the study indicate that the Implementation of the Active Emergency Village program in Realizing Community Independence in Roban Village, Singkawang Tengah District, Singkawang City has been implemented but has not been maximized. This can be seen from the implementation of the organizing process that has not been carried out in accordance with the activities of selecting the administrators and cadres of the Active Emergency Village through a special meeting of the formal leaders of the Village and community leaders and several community representatives. The election was carried out through deliberation and consensus, in accordance with the applicable procedures and criteria, facilitated by the Roban Health Center. The implementation of the interpretation process of the implementation of the socialization process through the transmission or distribution of information is not clearly received by the implementers such as the village head and the health center, so that not all people know or understand the program. The implementation of the application process such as the adequacy of implementing personnel, authority as authority or legitimacy for implementers in implementing the established policies is still limited, so the power of the implementors in implementing the program in the eyes of the community is not in accordance with the Decree of the Minister of Health of the Republic of Indonesia, Number 1529 / MENKES / SK / X / 2010 Concerning General Guidelines for the Development of Active Emergency Villages and Sub-districts.